Pengembangan Sistem Layanan Pembuatan buku Pelaut Online Menggunakan Metode Design Thinking dan Pendekatan Desain Prototipe Digital - Mahdani, Muhammad; Rahmawati, Maulidiah; Gupron, Akhmad Kasan; Dahri, Muh. (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to design an efficient and effective online seafarer's book publishing service system, besides that this research is also carried out to find out the enthusiasm of service users for the development of online seafarer's book publishing service services . The method used in designing the development of this system is design thingking. This method is used to find a solution to a problem by means of a collaborative process with potential users so that the resulting product can be in accordance with the needs and desires of the user. The results of the study show that a website-based user interface design is designed using figma and has been adapted to the needs of the user. The design was then tested using the Net Promoter Score (NPS) through a questionnaire accompanied by design drawings, which were assessed directly by the service users